Optimization of process conditions for extraction of biosurfactant - Jamal, Parveen; Alam, Md. Zahangir; Mohd Yusof, Umi Salmah; Wan Nawawi, Wan Mohd Fazli (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Biosurfactants are applied in many areas such as medical, food, industrial cleaning, bioremediation, personal care, and many more. However, its production involves high cost compared to synthetic surfactant,thus, the selection of raw material is critical in order to reduce the overall cost. In this study, waste raw material,palm oil sludge, has been used as a substrate. MTBE was selected as a potential solvent based on the value of surface tension, which was measured during screening process under controlled process conditions. In addition,optimization of the process conditions for solvent extraction was carried out with varied time, agitation and temperature using central composite design (CCD). The optimum conditions for extraction of biosurfactant are 4 hour, 150 rpm and 27ºC. This study, in effect, provided suitable solvent and optimum process conditions during solvent extraction for enhanced biosurfactant production.